О гетерогенности рода Bothriocephalus (Cestoda, Pseudophyllidea) - Корнюшин, В.В.; Кулаковская, О.П. (Вестник зоологии, 1984)
On Heterogeneity of the Genus Bothriocephalus (Cestoda, Pseudophyllidea). Kornyushin V. V., Kulakovskaya O. P.— Vestn. zool., 1984, No. 3. B. acheilognathi is transferred to the genus Clestobothrium, B. atherinae — to Pthychobothrium. Some other species, formerly assigned to Bothriocephalus, are transferred to these genera and to Oncodiscus and Penefrocephalus. The content of the genus Bothriocephalus is revised. The
rank of Pthychobothriidae is reduced to the subfamily level within Bothriocephalidac.